Trial of sex reverse percentage on female Shing (heteropneustes fossilis) by using 17?-Estradiol sex hormone (Research in Agriculture Livestock and Fisheries, 2015)
A study was conducted to evaluate the production of monosex (female) shing (Heteropneustes fossilis ) by using a sex hormone (17?-Estradiol). The experiment was composed of three treatments T1 (70 mg 17?-Estradiol /kg feed), T2 (80 mg 17? Estradiol /kg feed) and T3 (90mg 17?- Estradiol /kg feed) in duplicate were fed shing fishes in cemented cistern. The hormone was administered orally at variable doses with Tiger brand nursery fish feed (Eon Group) for 30 days. The fry were fed with the hormone mixed feed five times in a day. Every seven days intervals 50% water of the tanks were changed. A high mortality rate (47.6% to 67.4%) was observed in different treatments. The occurrence of female fish at the end of the experiment in treatment TI, T2 and T3 were 75%, 86%, and 96% female respectively. T3 (90 mg 17?-Estradiol /kg, feed) showed the best performance with 96% sex reversal to female progeny.Res. Agric., Livest. Fish.2(2): 313-317, August 2015